PENGARUH METODE QUANTUM LEARNING DAN PENGETAHUAN TENTANG LINGKUNGAN TERHADAP KEPEDULIAN LINGKUNGAN (Studi Eksperimen pada Pembelajaran Pengetahuan Lingkungan di Universitas Muhammadiyah Metro Tahun Akademik 2011/2012) - Agus Sujarwanta (Bioedukasi Jurnal Pendidikan Biologi, 2013)
The objective of this research was to analyze the effect of instructional methods and knowledge about the environment toward  environmental concern. The samples of the research were 60 students of biology education department, Muhammdiyah Metro University selected randomly. Data were collected using a valid instrument in form  questionare of environment concern and test of knowledge about environment with. Data were analyzed by using ANOVA 2 x 2. Findings of the research indicated that the environmental concern of students who were taught by quantum learning and had knowledge about the environment better than those who were taught using in conventional methods. Therefore, the quantum learning method  should be taken into consideration to increase the environmental concern on student with upper group of knowledge about the environment.Kata kunci: Kepedulian lingkungan, quantum learning, pengetahuan lingkungan